2023
DOI: 10.1111/jan.15718
|View full text |Cite
|
Sign up to set email alerts
|

Nursing informatics competence profiles and perceptions of health information system usefulness among registered nurses: A latent profile analysis

Abstract: AimsTo identify different nursing informatics competence (NIC) profiles in nurses, examine the factors associated with profile memberships and examine the associations of the derived profiles with the nurses' perception of the usefulness of a health information system (HIS).DesignA cross‐sectional study.MethodsA sample of 3610 registered nurses responded to a nationwide survey in March 2020. A latent profile analysis was performed to identify NIC profiles based on three competence areas: nursing documentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Overall, ethical competence related to digital solutions was evaluated quite highly in all profiles but not as highly as in previous research among nursing professionals (Kaihlanen et al, 2023;Saranto et al, 2022). Healthcare professionals' knowledge of ethical, legal and regulatory requirements as well as privacy and security issues related to digital solutions have been identified as major domains in several digital health competency frameworks and should be considered in training for all healthcare professionals (Nazeha et al, 2020).…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 52%
See 2 more Smart Citations
“…Overall, ethical competence related to digital solutions was evaluated quite highly in all profiles but not as highly as in previous research among nursing professionals (Kaihlanen et al, 2023;Saranto et al, 2022). Healthcare professionals' knowledge of ethical, legal and regulatory requirements as well as privacy and security issues related to digital solutions have been identified as major domains in several digital health competency frameworks and should be considered in training for all healthcare professionals (Nazeha et al, 2020).…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 52%
“…by Kinnunen et al (2019), in which general information technology competence in particular was found to be at a good level among healthcare professionals. Additionally, in a recent study by Kaihlanen et al (2023), the majority of registered nurses were included in either moderate or high nursing informatics competence groups. Finland (along with the Netherlands) has the most digitally competent citizens out of all European Union member states with 79% per cent of people having basic or above basic digital skills (European Commission, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a somewhat unusual phenomenon wherein the application of a practice has happened in advance of the evidence that supports it. Digital technologies are constantly evolving to improve access efficiency, safety and communication and in turn the scope of nursing informatics is rapidly evolving at the intersection of healthcare and information technology [3]. The adoption and optimization of electronic health records (EHR) continue to be a major focus in nursing informatics, with a growing knowledgebase on the importance of user-centered design to improve the usability and functionality of EHRs, ultimately leading to better care and safety [4].…”
Section: Introductionmentioning
confidence: 99%